Perkembangan Teknologi Multimedia di Era Postmodern dalam Pengaruhnya terhadap Ibadah Jemaat GMIM Genesaret Pateten - Kristo Mewengkang; Maria E. Tulangouw; Vanny N. Suoth (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research discusses the development of multimedia technology in the postmodern era and examines its profound influence on the life of the church. In this era, the presence of multimedia technology provides both new opportunities and complex challenges for the church in carrying out its mission and maintaining the relevance of its message. The study emphasizes that technology can serve as a bridge between tradition and modernity, helping the church to communicate values of faith more effectively to the congregation and the wider public. The research applies a qualitative approach with data collection techniques that include direct observations in the field, in-depth interviews, and analysis of related phenomena obtained from relevant sources. The findings highlight that multimedia technology has the potential to become an important mediator in connecting the context of contemporary life with the growth of the congregation’s faith, especially in worship practices, spiritual formation, and outreach activities. Thus, technology is not only a tool but also a partner in ministry.